PEMETAAN DAN VALUASI EKONOMI KERUGIAN BANJIR DI KARESIDENAN SURAKARTA - Suryanto . (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2017)
Negative impact of Cilmate change as current environmental issues could not be avoided. Climate change causedloss especially for agricultural sector. The purposes of research: 1) to mapping and identify flooding area, 2) toestimate negative loss of climate change to decreasing of farm production and farmer income.This study used quantitative approfach to estimate probability loss in agricultural land. Tool of analysis tomapping and identify the vulnerable area relied on Geographic Information. Spatial data would be needed in thisresearch to give information about the area. Economic valuation would give result value loss of production causedof climate change impact.Result of data analysis showed that most of regencies in Karesidenan Surakarta have vulnerable area of flood.These regencies were Kota Surakarta, Kabupaten Sragen, Karanganyar, Sukoharjo, and Klaten. The other regenciessuch as Boyolali and Wonogiri could be classified as less vulnerable to flood hazard. Based on economic valuationgave result that 36.72 percent to total of agricultural land vulnerable toward flood and 24.55 percent to total ofagricultural land vulnerable toward drought.